Compact Heat Exchangers : Selection, Design and Operation. (Butterworth-Heinemann, 2016)
Compact Heat Exchangers: Selection, Design, and Operation, Second Edition, is fully revised to present the most recent and fundamental ideas and industrial concepts in compact heat exchanger technology. This complete reference compiles all aspects of theory, design rules, operational issues, and the most recent developments and technological advancements in compact heat exchangers. New to this edition is the inclusion of micro, sintered, and porous passage description and data, electronic cooling, and an introduction to convective heat transfer fundamentals. New revised content provides up-to-date coverage of industrially available exchangers, recent fouling theories, and reactor types, with summaries of off-design performance and system effects and installations issues in, for example, automobiles and aircraft. Hesselgreaves covers previously neglected approaches, such as the Second Law (of Thermodynamics), pioneered by Bejan and co-workers. The justification for this is that there is increasing interest in life-cycle and sustainable approaches to industrial activity as a whole, often involving exergy (Second Law) analysis. Heat exchangers, being fundamental components of energy and process systems, are both savers and spenders of energy, according to interpretation.
Keywords: Heat exchangers.; elektronické knihy; electronic books